Geographical, temporal, and individual‐based differences in the trophic ecology of female Cape fur seals. Issue 2 (8th February 2023) - Botha, Jonathan A.; Trueman, Clive N.; Kirkman, Stephen P.; Arnould, John P. Y.; Lombard, Amanda T.; Connan, Maëlle; Hofmeyr, G. J. Greg; Seakamela, S. Mduduzi; Pistorius, Pierre A.
Abstract: Information on resource use and trophic dynamics of marine predators is important for understanding their role in ecosystem functioning and predicting population‐level responses to environmental change. Where separate populations experience different local environmental conditions, geographic variability in their foraging ecology is often expected. Within populations, individuals also vary in morphology, physiology, and experience, resulting in specialization in resource use. In this context, isotopic compositions of incrementally grown tissues such as keratinous hairs offer a valuable opportunity to study long‐term variation in resource and habitat use. We investigated the trophic ecology of female Cape fur seals ( Arctocephalus pusillus pusillus ) using carbon and nitrogen isotopic compositions of serially sampled whiskers collected at four breeding sites along the coast of South Africa. Drawing on over 900 isotopic measurements, we assessed geographic variability in isotopic niche width between colonies and the degree of individual specialization. We found slight, but clear geographic differences in isotopic ratios and isotopic niche widths, seemingly related to ecological setting, with niche widths being proportional to the area of available shelf and shelf‐slope habitat surrounding the colony. We further identified periodic oscillations in isotopic ratios, which likely reflect temporal patterns in foraging distribution and prey type, linked to shifts in the availability of prey resources and their interaction with constraints on individual females throughout their breeding cycle. Finally, individual specialization indices revealed that each of the study populations contain specialist individuals that utilize only a small subset of the total population niche width. The degree of individual specialization was, however, not consistent across colonies and may reflect an interactive influence between density‐dependent effects and habitat heterogeneity. Overall, this study provides important information on the trophic ecology of Cape fur seals breeding in South Africa and highlights the need to consider geographic and individual variability when assessing the foraging ecology of marine predators. Abstract : Using stable isotope compositions of serially sampled whiskers, this paper provides a detailed assessment of Cape fur seal trophic ecology across four South African breeding colonies. We focus on geographic differences in diet and habitat use, long‐term temporal trends in isotopic signatures, and geographic differences in individual specialization. Our results highlight clear geographical gradients in the isotopic composition of whiskers, which support recent evidence of spatial differences in habitat use and foraging strategies.